Pengaruh Profitabilitas dan Sales Growth Terhadap Penghindaran Pajak Perusahaan Batubara Tahun 2015-2019 - Alda Arthauli Sitohang (P4M STIE Putra Bangsa, 2021)
This research aims to examine how profitability and growth of companies will affect coal company tax avoidance in 2015-2019. This type of research uses initiative with secondary data from the data of financial and annual reports of coal companies in 2015-2019. The research sample was obtained from 22 coal companies from 2015-2019, with 110 research samples found. Data analysis techniques use statistical analysis from SPSS software such as descriptive statistical analysis, correlation coefficient, determination coefficient, significant F and t-tests, multiple linear regression and analysis classic assumption test. The results of this study show that there is a significant influence between profitability and the measure of sales growth on tax avoidance judging by the F-count value of 4,341 there is a p-value of < 5% (Sig. 0.016).